2010
DOI: 10.1111/j.1365-2893.2009.01233.x
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and individualized treatment to achieve sustained viral response for recurrent hepatitis C in liver transplant recipients

Abstract: Hepatitis C recurrence after liver transplantation is universal and is a major cause of long-term graft failure. Improving the effectiveness of recurrent hepatitis C treatment is extremely important. We studied 35 anti-hepatitis C virus (HCV)-positive patients who underwent liver transplantation. Among the 35 patients, 25 patients had recurrent hepatitis C and received antiviral treatment. HCV RNA load after liver transplantation was increased by 3.68-fold. The antiviral treatment regimen comprised pegylated-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Most available data come from uncontrolled studies with different designs regarding time to start treatment, regime used and follow‐up. Therefore, the results are also very different, with SVR rates ranging between 20% and 50% with an average around 30% . These results are lower than those obtained in non‐transplanted patients, possibly because of the immunosuppressive status, the high prevalence of HCV genotype 1‐infected patients, the typical high viral load and the difficulty in maintaining adequate antiviral doses, especially RBV, and maintaining therapy for the ideal duration.…”
Section: Post‐transplant Antiviral Treatmentmentioning
confidence: 90%
“…Most available data come from uncontrolled studies with different designs regarding time to start treatment, regime used and follow‐up. Therefore, the results are also very different, with SVR rates ranging between 20% and 50% with an average around 30% . These results are lower than those obtained in non‐transplanted patients, possibly because of the immunosuppressive status, the high prevalence of HCV genotype 1‐infected patients, the typical high viral load and the difficulty in maintaining adequate antiviral doses, especially RBV, and maintaining therapy for the ideal duration.…”
Section: Post‐transplant Antiviral Treatmentmentioning
confidence: 90%
“…The 19 reviewed studies showed a mean end-of-treatment response of 42% and a mean overall SVR of 30%. A recent study [ 122 ] disclosed an SVR rate of 64% in DDLT patients. The antiviral treatment regimen comprised pegylated-IFN (180 μ g) every 2 weeks and RBV at a dose of 200 to 400 mg every day.…”
Section: Treatment For Established Infectionmentioning
confidence: 99%